Cysteine residues reduce the severity of dopamine electrochemical fouling. (20th August 2016) - Harreither, Wolfgang; Trouillon, Raphaël; Poulin, Philippe; Neri, Wilfrid; Ewing, Andrew G.; Safina, Gulnara
Highlights: Cysteine containing molecules decrease the dopamine induced fouling of the electrodes made of carbon based materials. Albumin reduces the impact of dopamine fouling in a dose-dependent manner. Mechanism of the protective effect of thiols of the rate of dopamine polymerization on the electrode surface is discussed. Solutions of albumin as a background for calibrating electrochemical sensors is suggested for certain experiments. Abstract: The fouling of neurotransmitter during electrochemical detection can dramatically jeopardize the viability of the sensor. Several recent developments in electrode fabrication and design have helped mitigating this issue. For instance, carbon nanotube fiber (CNTF) electrodes were found to be more resistant to fouling than the traditional carbon fiber (CF) electrodes. Here, we investigate the fouling resistance of these two materials in the presence of albumin. Interestingly, our data shows that the presence of albumin reduces the impact of dopamine (DA) fouling in a dose-dependent manner. A protective effect from DA fouling was also observed for other thiol containing substances, thus hinting that the sulfur competes with the amine moiety for the nucleophilic binding to the oxidized catechol, a critical step initiating DA fouling, and therefore reduces the rate of DA polymerization on the electrode surface. Overall, this study furthers our understanding of the mechanisms controlling DA detection in situ, and suggests using solutions of albumin as a background for calibrating sensors.